The Theory and Practice of Customer Loyalty Management and Customer Focus in the Enterprise Activity - Kiseleva, Elena M.; Nekrasova, Marina L.; Mayorova, Marina A.; Rudenko, Marina N.; Kankhva, Vadim S. (International Review of Management and Marketing, 2016)
Nowadays in Companies paid much attention to client relationship management. In modern conditions there is an unclear distinction between the terms “customer loyalty” and “brand loyalty”. They were developed at different times and within different concepts: the term “brand loyalty” was coined in the early 20-ies in the United States and was developed in the framework of the branding concept, and the term “customer loyalty” began to develop actively in the 80 -e years. Currently, brand loyalty – is one of the types of customer loyalty, developed mainly for consumer goods, so the methodology developed for this area, is of limited use and the concept, defining all the category of customer loyalty, should be regarded as “consumer loyalty”. Consumer loyalty is divided into behavioral and perceived. Monitoring behavioral loyalty is carried out by observing the actual behavior of the client and is the method of implementation of a retrospective transactional analysis of its consumer activity. Emotional loyalty of customers is reflected in their level of awareness about the organization and about their needs they can satisfy, taking advantage of its products or services, as well as in the level of customer satisfaction with the company's offerings, their quality and service provided by the organization. In addition, an important component of perceived customer loyalty is the emotional level of customer's perception of the company. For the most complete and comprehensive assessment, it is the most appropriate to use an approach that involves monitoring of both behavioral and perceived of customer loyalty. Keywords: loyalty management, marketing, customer JEL Classifications: L81, L84, M31